Application of TRIZ to Develop New Antistatic Materials - Jiang, Jie; Li, Yan (Asian Journal of Chemistry, 2012)
In this paper, the existing methods to increase the electrical conductivity of the materials were analyzed. Then the technical conflict solution derived from TRIZ was used to realize the innovation of the antistatic agent. According to the invention principles, DEP with high boiling point, low volatility, good compatibility with PVC and a good solubility of alkali metal salts has been designed and successfully synthesized. Then an antistatic agent with high electrical conductivity was obtained by doping alkali metal perchlorates to DEP. After using DEP/NaClO4 as a new plasticizer, the PVC/DEMP/NaClO4 composite was obtained. Whose surface resistivity was decreased sharply with the increase of the DEP/NaClO4 content. The surface resistivity can drop to 107.6 Wsq-1 (25 ºC, 0.1 % RH) when the DEP/NaClO4 content was 60 phr.